Analisis Metode Pengendalian Kualitas Produk sebagai Pencegahan Kegagalan Produksi: A Literature Review - Siallagan, Sahala; Diomen Syahputra Manik (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2024)
In the manufacturing industry, quality plays an important role as a criterion for assessing industrial readiness. In the production process, failure to meet product standards often results in defective or damaged products. Therefore, companies should prevent and reduce the number of defective products that do not meet standardization provisions. The purpose of the study is to develop theoretical and practical aspects of the analysis of product quality control methods for product failure prevention. This study is a literature review by means of a library data collection published nationally in the past ten years, especially in Industrial engineering. The results show that the Failure Mode and Effects Analysis (FMEA) method is most frequently used in quality control studies. The FMEA may prevent the failures that arise so that product failures can be reduced, which increases the company's revenue. This method can be compared with other similar studies for further analysis. Combining FMEA with other methods can be considered a novelty that can be utilized to increase the business of both products and services in society, especially in small and medium enterprises.